I'm guessing your problem is this:
y³ - 9y² + y - 9 = 0
right?
In solving this problem, I recommend doing this:
y³ - 9y² + y - 9 = 0
Factor out a y² from the first two numbers in the problem:
y²(y - 9) + (y - 9) = 0
Separate the parentheses which means y - 9 goes on one side. The y² added a one since it came from the + 1 in the middle of expression. When you're separating parentheses like this you just take the outside numbers and combine them together. Since + 1 came from the outside of the (y - 9) and y² also was sitting on the outside of (y - 9) combine them to make y² + 1. Like this:
(y² + 1)(y - 9) = 0
Now separate your two parentheses to two separate problems:
(y² + 1) = 0 and (y - 9) = 0
Now you're y² + 1 will equal:
y² = -1
y = √-1 <-- This number doesn't exist so it will be an imaginary number (i). If you guys didn't learn that in your class I recommend just leaving it as i for that part.
Now solve y - 9 = 0:
y = 9 <-- Since we added nine to both sides to get this.
So you're final answer should be y = i and 9
Answer:
-1 and -4
Step-by-step explanation:
-1 + -4 = -5
-1 times -4 = 4
give brainiest please!
hope this helps ;)
Answer:
a² + 4ab + 4b²
Step-by-step explanation:
Given
(a + 2b)²
= (a + 2b)(a + 2b)
Each term in the second factor is multiplied by each term in the first factor, that is
a(a + 2b) + 2b(a + 2b) ← distribute both parenthesis
= a² + 2ab + 2ab + 4b² ← collect like terms
= a² + 4ab + 4b²
Answer:
The similarity statement: FGHI ~ BCDE
Similarity ratio: 5:1
Step-by-step explanation:
The similarity statement is quite obvious, as there are only two rectangles shown, and the other one is "BCDE".
The similarity ratio is 5:1 because everything in the 1st (FGHI) rectangle is multiplied 5 times the values in the 2nd (BCDE) rectangle.